APPLICATION OF THE MAKE A MATCH MODEL ASSISTED WITH ESAPI MEDIA TO IMPROVE STUDENTS’ LEARNING OUTCOMES - Nita Yunda Sari; Ika Oktavianti; Deka Setiawan (PROGRES PENDIDIKAN, 2021)
This research aims to describe the application of the model a make a match assisted by ESAPI media to improve student learning outcomes in grade IV SDN Wonoketingal 02. Classroom action research was conducted in class IV SDN Wonoketingal 02 with a research subject of 20 students. This study uses design classroom action research from Kemmis and MC. Taggart and last for 2 cycles. The independent variable of this study is the make a match model and ESAPI media, while the dependent variable in this study is student learning outcomes. Data collection methods used are qualitative and quantitative data. The result showed an increase in mastery learning outcomes aspects of knowledge in the first cycle of 73.3% and an increase in the second cycle of 77.2% in good qualifications. The completeness of both cycles is 3.9% with a good category. This proves that the application of the make a match model assisted by ESAPI media can improve student learning outcomes in grade IV SDN Wonoketingal 02.